Pengaruh Latihan Karet Ban Terhadap Kecepatan Tendangan Dollyo Chagi Pada Atlet Taekwondo Di Dojang Star Club Kota Bengkulu - Suwarningsih, Bunga Tri; Asnawati, Asnawati; Martiani, Martiani (Educative Sportive, 2024)
The purpose of this study was to influence the effect of rubber tire training on Dollyo chagi kick speed. Taekwondo athletes at Dojang star club Bengkulu City. The method used in this research is descriptive quantitative research this research design is in the form of experiments with the form of one group pretest and postest. The sample in this study were 35 taekwondo athletes Dojang star Club Bengkulu. The results of this study found that there was an increase in the results of dollyo chagii kicks after being given training using rubber tires. This is evidenced by the increase in the average kick results of the research sample. The average pretest kick was 51.25 while the average postest result was 60.11 from this value it can be seen that there was an increase in test results of 8.86. Based on the results of multiple linear regression tests, the effect of using rubber tires on dollyo chagi kick speed has an R Square value of .898, indicating a very strong influence. Meanwhile, based on the results of the hypothesis test, it is known that the significant value of 0.004 indicates that 0.04 ≤ 0.05 so that the results of this hypothesis test show a significant effect between the pretest and posttest results, meaning that there is a significant effect of using rubber tires on the speed of dollyo chagi kicks at dojang star club athletes in Bengkulu city. So it can be concluded that the use of rubber tire media in increasing the speed of dollyo chagi tendengan is proven by the increase in test results after treatment.